Changing the game : my career in collegiate sports marketing - Host, Jim, 1937- (The University Press of Kentucky, 2020)
"Many Kentuckians, especially those involved in intercollegiate athletics, have heard the name Jim Host. But few, even those influenced by his professional accomplishments, know his full story. Host played a crucial role in the development of collegiate sports. Taking on numerous responsibilities, including major roles in sports broadcasting, marketing, real estate, higher education, and politics, he always maintained sports as a priority and worked to increase the exposure of collegiate sports. Enrolling at the University of Kentucky in 1955 on one of the first two baseball scholarships offered by the institution, Host went on to sign with the Chicago White Sox as a pitcher where he spent one year before suffering a career-ending shoulder injury. In 1971, following a successful real estate business and a stint in Governor Louie B. Nunn's administration, Host began what would eventually become Host Communications, Inc, bringing together some of the best in sports marketing and broadcasting. After purchasing the radio broadcasting rights in 1974 to University of Kentucky football and basketball games, his company then secured the rights to create the NCAA Radio Network to broadcast the men's college basketball tournament. In 1983, Host and his team introduced what became known as the NCAA's Corporate Partner Program and in 1985, the first collegiate corporate marketing program was implemented. Employing companies such as Gillette, Valvoline, Pepsi, American Airlines, Pizza Hit, KFC, and Taco Bell to promote university athletic programs and the NCAA at large, Host changed the game of college sports marketing and dramatically escalated the revenue generated at universities across the country. In Changing the Game, Host, with the help of coauthor Eric A. Moyen, presents the first complete account of the entrepreneur's professional life. Host's influence on college sports is made evident as he tells stories of his involvement in sports radio, management, broadcasting, marketing, and more, highlighting important figures in Kentucky's sports history and his interaction with them along the way. Host's firsthand description gives an exclusive detailed perspective and allows the readers access into the moments that helped shape the fans' experience"--